2018
DOI: 10.29252/beat-060403
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Road Traffic Injuries among Elderly People; A Systematic Review and Meta-Analysis

Abstract: Objective:To systematically review the epidemiological patterns and interventions for prevention of road traffic injuries (RTIs) among elderly. Methods:Searching keywords including: accident, trauma, road injury, road traffic injuries, aging, old, elder, strategy, intervention, road traffic crash prevention and traffic accident in databases including, Google scholar, SID, IranMedex, PubMed and Scopus. English and non-Persian articles, articles presented in congresses, articles that considered elderly people to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 55 publications
1
46
0
4
Order By: Relevance
“…The GCS is well correlated with fatality after head injuries. A systematic review and meta-analysis of trauma patients reported that older patients had higher mortality than younger patients 42,43 . Older patients have higher mortality and morbidity than younger patients, even in MVCs of equal severity 44,45 .…”
Section: Non-fatal Fatalmentioning
confidence: 99%
“…The GCS is well correlated with fatality after head injuries. A systematic review and meta-analysis of trauma patients reported that older patients had higher mortality than younger patients 42,43 . Older patients have higher mortality and morbidity than younger patients, even in MVCs of equal severity 44,45 .…”
Section: Non-fatal Fatalmentioning
confidence: 99%
“…Interestingly, children under 12 years are not able to use visual and vestibular information as effectively as adults [34,35]. Similarly, the elderly are also more susceptible to PIs and subsequent mortality due to a reduced reflex time, decreased sensory-motor coordination, and age-related auditory and visual impairment, resulting in a slow walk time when crossing streets [29,[36][37][38][39]. In addition, we are seeing a rise in geriatric injury as the population ages [28].…”
Section: Discussionmentioning
confidence: 99%
“…There are various mechanisms and causes of PIs that are mentioned in the literature. Motorcycle collisions with pedestrians are highlighted as being responsible for the majority of deaths [20,34,39,40,42]. However, some studies highlight other factors such as buses, trucks, freeways, weather conditions, time of day, road density, lack of appropriate signaling, zebra crossings, crossing the highway, walking on the pavement, bus stops, and speed [27,29,38,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Children under 12 years are not able to use visual and vestibular information as effectively as adults [31,32]. Similar to children, the elderly are susceptible to PIs and their fatal complications due to a reduced reflex time, decreased sensorymotor coordination, and the associated auditory and visual impairment of age, resulting in a slow walk time when crossing streets [26,[33][34][35][36]. Geriatric injury increases as the population ages [25].…”
Section: Discussionmentioning
confidence: 99%